Development of the American College of Rheumatology Electronic Clinical Quality Measures for Gout. Issue 5 (12th April 2018) - FitzGerald, John D.; Mikuls, Ted R.; Neogi, Tuhina; Singh, Jasvinder A.; Robbins, Mark; Khanna, Puja P.; Turner, Amy S.; Myslinski, Rachel; Suter, Lisa G.
Abstract : Objective: Electronic clinical quality measures (eCQMs) are increasingly used by health registries and third parties to evaluate and improve the quality of health care. To complete these eCQMs, data are extracted from electronic health records (EHRs). The treatment of gout has been an area identified with gaps in quality of care. On behalf of the American College of Rheumatology (ACR), we sought to develop and test eCQMs to evaluate gout care. Methods: Drawing from the 2012 ACR gout guidelines, a working group developed candidate gout process measures that were evaluated by an interdisciplinary panel of health care stakeholders, the ACR Quality Measures Subcommittee (QMS), and ultimately the ACR Board of Directors for formal validity testing. For each of the selected gout eCQMs, 3 clinical sites using different EHR systems tested the scientific feasibility and validity of the measures. Measures appropriate for accountability were presented for national endorsement. Results: Of the 10 proposed eCQMs, 4 were endorsed by the ACR QMS, 3 were incorporated into the ACR's Rheumatology Informatics System for Effectiveness (RISE) Registry, and 2 were endorsed by the National Quality Forum. The 3 eCQMs incorporated into RISE (evaluating indications for urate‐lowering therapy [ULT]), monitoring serum urate, and treat‐to‐target outcome) demonstrated high validity and reliability. Proportions of patients passing these 3 eCQMs in RISE and at the 3 clinical testing sites ranged between 32% and 58%, indicating significant room for improvement in care. Conclusion: Three eCQMs have been validated and implemented into RISE. Two of these measures (evaluating indications for ULT and monitoring serum urate) are available for use in federal quality reporting programs. Performance on these measures suggests there is significant room for improvement in the management of gout.